1970
DOI: 10.1159/000157829
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Distension and Acetylcholine on Intestinal Blood Flow <i>in vivo</i>

Abstract: In vivo canine gut segments perfused by branches of the superior mesenteric artery were subjected to increased intraluminal pressure to observe the effects upon arterial inflow, measured with an electromagnetic blood flowmeter, and venous effluent collected by a cannula. Inflation of the intestinal segment with air simultaneously reduced both inflow and outflow. Intra-arterial infusion of acetylcholine increased blood flow, even with intraluminal pressure maintained at 40 mm Hg. Mechanical distension of the gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
3
0

Year Published

1970
1970
1989
1989

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
(21 reference statements)
4
3
0
Order By: Relevance
“…The present study reconfirms the observations of several investigators showing that distension interferes with intestinal hemodynamics [1,3,6,7,[13][14][15][16]. While most of the authors reported hemodynamic impairments only for intraluminal pressures higher than 25-30 mm Hg, the present re sults show that an increase in vascular resistance is still observed for in traluminal pressures of near 10 mm Hg.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study reconfirms the observations of several investigators showing that distension interferes with intestinal hemodynamics [1,3,6,7,[13][14][15][16]. While most of the authors reported hemodynamic impairments only for intraluminal pressures higher than 25-30 mm Hg, the present re sults show that an increase in vascular resistance is still observed for in traluminal pressures of near 10 mm Hg.…”
Section: Discussionsupporting
confidence: 92%
“…While most of the authors reported hemodynamic impairments only for intraluminal pressures higher than 25-30 mm Hg, the present re sults show that an increase in vascular resistance is still observed for in traluminal pressures of near 10 mm Hg. Moreover, the vascular respon ses lasted as long as the distension, without readjustment of the vascular resistance, as reported by several authors [3,7,13]. The experimental conditions were different in so far as the distension was performed by in jecting into the gut lumen a constant volume of liquid or gas, whereas in the present study the intraluminal pressure remained constant.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…On the other hand, under pre-and postganglionic stimulation after reserpinization, M a u sk o pf et al [1969] observed a-adrenergic blockade and application of guanethidine vasodilations with a successive escape on the vascular bed of the dog's skeletal muscle. Like other authors [D jo jo su g ito et al, 1968;Shehadeh et al, 1969;Brobman et al, 1970] they did not observe humoral cholinergic-induced escapes. The reason for this contrast to our results may lie in their insufficient doses of Ach, for the escape is strongly dose-dependent ( fig.…”
Section: Discussionsupporting
confidence: 74%
“…These results are in contrast to those of F o l k o w et al [1961] and D o r r and Brody [1965]. However, these authors did not find an escape reaction from vasodilation induced by in fusion of acetylcholine (Ach) in the vascular bed of skeletal muscle, nor did Shehadeh et al [1969] and Brobman et al [1970] do so in the intestinal circulation.…”
mentioning
confidence: 57%